Implementing Circular economy practices in organic farms, in North Greece. Present status and recommendations for advancement - Marnasidis Symeon; Kesisoglou Ilias; Verikouki Efstathia (E3S Web of Conferences)
Despite facing numerous challenges since the early 1990s, Greek organic farming has managed to expand its cultivated areas and establish itself as an economically viable production system. Various organic production practices, help farmers to achieve a circular flow of materials and resources. This study focuses on exploring the level of adoption of Circular Agriculture (CA) practices from Greek organic farms, assessing the effect of four primary barriers to their adoption, while also proposing strategies for further development. The expert’s opinions survey showed that Organic agricultural practices, enable Greek organic farmers to attain a moderate level of circular flow of materials and resources, with significant potential for further improvement. Critical steps towards embracing the concept of circularity, include promoting applied research and establishing a knowledge network about compatible CA practices, strengthening organic agricultural cooperative schemes and establishing renewable energy systems on organic farms. Agricultural subsidies, could also support the adoption of rarely applied CA practices. Our findings could serve as a valuable foundation for exploring the relationship between Greek organic farming and circular agriculture. This study also highlights several knowledge gaps in adopting innovative CA practices under the Greece farming conditions and thus providing insightful information for policy making on CA.